Synthesis of dark orange montmorillonite/g-C3N4 composites and their applications in the environment. (August 2017) - Li, Pengpeng; Huang, Liying; Li, Yeping; Xu, Yuanguo; Huang, Shuquan; Yuan, Ding; Xu, Hui; Li, Huaming
Abstract: Dark orange montmorillonite/g-C3 N4 composites were prepared through a conventional calcination route. The obtained samples were analyzed by XRD, TEM, TG, XPS, FT-IR, DRS, Photocurrent-time and PL measurements. The photocatalytic performance of montmorillonite/g-C3 N4 composites was assessed by the methylene blue (MB) degradation. Compared to pure g-C3 N4, the obtained photocatalysts displayed outstanding photocatalytic activity. The improved photocatalytic activity was ascribed to the improved absorbance in the visible light range and favorable adsorptive capacity to MB dye. The electron spin resonance (ESR) analysis and trapping experiment showed that O2 − and h + played a major role in the decomposition of MB. In addition, it was found that montmorillonite/g-C3 N4 (0.5) composite had a new property, which showed that it can be applied as a sensor in the photoelectrochemical detection of trace amount of Cu 2+ . Graphical abstract: Dark orange montmorillonite/g-C3 N4 composites were synthesized through a conventional calcination method. The composites displayed superior photocatalytic activity under visible light irradiation. The improved photocatalytic performance is attributed to the enhanced visible light absorbance and good adsorptive capacity to dye. It was found that O2 − and h + played a major role in photocatalytic degradation process. Further studies showed that the composite could also be used for the detection of trace amounts Cu 2+ . It is a new but promising candidate for the application in the water environment. Highlights: Dark orange montmorillonite/g-C3 N4 composites had been successfully synthesized via a calcination method. The montmorillonite/g-C3 N4 composites exhibited improved photocatalytic performance in the degradation of methylene blue. The improved photocatalytic performance is due to an enhanced visible light absorbance and good adsorptive capacity to dye. The montmorillonite/g-C3 N4 composites could be used for the detection of trace amounts Cu 2+ .